Genome assembly of the Ringed seal Pusa hispida ... - Nebenführ, Marcel; Arnason, Ulfur; Janke, Axel (GigaScience Database, 2024)
The ringed seal ( Pusa hispida ) ranks among the smallest species within the phocid family. Its designation is derived from the distinctive light-colored rings that adorn its otherwise dark back. Ringed seals are found in the Arctic region, the Sea of Okhotsk, the Baltic Sea, and specific freshwater lakes in Russia or Finland. The total population of ringed seals remains largely uncertain but studies suggest that approximately 3.5 million individuals exist. We present a publicly available genome assembly of the Ringed seal Pusa hispida , with 37 Gb (~17.3-fold coverage) of sequence data. The complete assembly spans 2.3 Gb, with contig N50 of 13 kb and scaffold N50 of 173 Mb. The BUSCO analysis indicates a completeness of 89.5%. ...